Family routines within the ecological niche: an analysis of the psychological well-being of U.S. caregivers of children with disabilities - Larson, Elizabeth; Miller-Bishoff, Thomas (Frontiers in Psychology, 2014)
Using mixed methods, this study examined the relationship of caregivers of children with disabilities’ psychological well-being and their orchestration of daily routines within their ecological niche. Thirty-nine U.S. caregivers completed in-depth interviews, Psychological Well-being Scales (PWB), and Family Time and Routines Index (FTRI). We used a multi-step analysis. Interview data was coded and vignettes created without knowledge of PWB and FTRI ratings. Next, the relationship of quantitative measures was analyzed. Four groups were created using FTRI-extent and PWB means: (1) low routine-low PWB, (2) low routine-high PWB, (3) high routine-low PWB, and (4) high routine-high PWB. We examined qualitative differences in key features between groups. Findings: Total PWB and FTRI scores were not significantly correlated, PWB Purpose in Life and FTRI-extent scores were moderately positively correlated, and PWB Environmental Mastery and FTRI-extent correlation approached significance. Qualitative findings describe caregivers’ structuring of routines, intensity of oversight, support in routines, management of dinner, paid work, and needs for respite. The four groups differed in paid work, household support, degree the child could self-occupy, Environmental Mastery, and opportunities to recuperate. Caregivers with higher levels of well-being and more regular routines did paid work, had supportive spouses, had children who more often could follow routines, had higher Environmental Mastery, could orchestrate a family meal, and had breaks from care in either work or leisure. All Native American caregivers and Mexican American caregivers with spouses were in the high routine-high PWB group. Insight into this complex negotiation between family members within daily routines may provide practitioners a better understanding of how to work within family circles to foster therapeutic alliances, identify focused intervention targets, and promote positive family-wide outcomes.